REGULATION OF MICRO PLASTICS AND PRIORITY POLLUTANTS IN SURFACE WATER BODIES BASED ON BASIN PERMISSIBLE CONCENTRATIONS (BPC) - Chernaya, Violetta; Blinova, Eleonora (Journal of the Belarusian State University. Ecology, 2026)
A multi-year analysis of the ecosystem and sanitary-hygienic functions of Russian cities shows that the ecosystem «benefits», which are only possible under proper environmental and hygienic management, are losing their function year by year. Statistical data on discharges and concentrations of hydropollutants do not fully reflect the actual situation regarding the quality of surface waters in the Russian Federation: information describing the volumes and dynamics of pollutant discharges into water bodies is often presented in a generalized form. As a result of an in-depth study and analysis of the existing system for environmental assessment of surface waters and the list of evaluated pollution indicators, we have developed proposals for introducing basin permissible concentrations (BPC) and regulating plastic particle pollution. «Microplastic» is not enshrined in the environmental regulations of the Russian Federation, and efforts to include this parameter in the regulatory system are of an innovative nature. A new concept of regulation is proposed, taking into account the regional characteristics of water catchments, as well as methodological approaches to laboratory control of microplastics. The organizational, legal, and environmental aspects of implementing this approach in the water management system of the Russian Federation are considered. In order to include microplastics in the list of controlled indicators, it is necessary to develop and approve a measurement methodology using Fourier transform infrared (FTIR) spectroscopy and/or Raman spectroscopy. The article observes the priority pollutants in surface water from different regions of Russia, and presents the main environmental problems of major watercourses in the basin districts and hydrographic regions of the Russian Federation, based on the analysis of hydrochemical information from the State Observation Network (SON) of the Federal Service for Hydrometeorology and Environmental Monitoring (Roshydromet) for the period from 2021 to 2024. A long-term analysis of the urban ecosystems sustainability and of the sanitary and hygienic monitoring organization shows that the preservation of ecosystem «benefits» and comfort is possible only with proper environmental management of territories (including river basins).